Dependence on Central Transfer Funds in Alleviating Poverty in Districts/Cities Papua Province - Nusa, Yahya; Sanusi, Anwar; Supanto, Fajar; Pabendon, Tharsisius; Sandy, Stepanus (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to analyze whether poverty alleviation in the Districts/Cities of Papua province can be influenced by Regional Original Income or still depends on central transfer funds. The research method is panel data analysis with Fixed Effect Model (FEM) approach using EViews12. The results showed that Regional Original Income did not have a significant effect on poverty in the Districts/Cities of Papua Province, while the Balancing Fund and Special Autonomy Fund had a significant effect on poverty in the Districts/Cities of Papua Province. This shows that in alleviating poverty in the Districts/Cities of Papua province still depends on central transfer funds, namely the balance fund and special autonomy funds.